Analysis of Front Office's Role in Managing Guest Voice to Increase Guest Satisfaction at Natra Bintan a, Tribute Portfolio Resort - Andres Ferdana Putra; Rahmi Fadilah (Journal of Multidimensional Management, 2025)
This study investigates the role of the Front Office in managing guest voice to enhance guest satisfaction at Natra Bintan, a Tribute Portfolio Resort. Using a descriptive qualitative approach, data were collected through semi-structured interviews with Front Office staff, direct observations, and documentation review, and validated using methodological triangulation. The findings reveal that the Front Office plays a central role in facilitating communication between guests and management, addressing complaints promptly, and implementing service improvements based on guest feedback. Key functions identified include guest reception, complaint resolution, service personalization, and follow-up actions, which collectively contribute to positive guest experiences. The study highlights that effective guest voice management not only increases satisfaction but also strengthens guest loyalty and brand image in the competitive hospitality sector. Theoretically, this research extends role theory by demonstrating how frontline staff can function as mediators of service quality perception through systematic feedback handling. Practically, it provides actionable insights for hotel managers to integrate structured guest voice management systems into service operations. This integrated approach can serve as a strategic tool to enhance service excellence and maintain competitiveness in the hospitality industry.